Methodology for Prevention Through Design in Occupational Safety - Trajce Velkovski; Jasmina Chaloska; Zlatko Petreski; Aleksandra Hristova (Faculty of Technical Sciences, University of Novi Sad, Serbia, 2023)
Individual motivation plays a fundamental role in shaping human behavior, and this holds true for employees within the realm of occupational health and safety (OHS). Consequently, comprehending employee motivation from various levels and perspectives within organizations assumes paramount importance. Among the crucial components of Occupational Health and Safety Management Systems (OHSMS) within organizations, as well as OHS more broadly, are the OHS trainings provided to employees. This research aims to characterize the qualitative dimension of employee motivation, drawing upon the framework of the Self-Determination Theory (SDT), in manufacturing organizations located in the Republic of Macedonia. The findings of this study aim to contribute to a deeper understanding of employee motivation and aid in the enhancement of organizational approaches to the design of OHS trainings. The identification of qualitative dimensions of employee motivation, as per the principles of SDT, is grounded in the analysis of existing scientific and research literature, supplemented by a survey conducted among a sample of 70 employees.
Keywords: employee OHS trainings, motivation, Self-Determination Theory, qualitative dimensions of motivation, manufactory industry, work accidents